Purification of low‐abundance lysozyme in egg white via free‐flow electrophoresis with gel‐filtration chromatography. Issue 16 (24th June 2020) - Dong, Shuang; Jiang, Ziqin; Liu, Zhen; Chen, Ling; Zhang, Qiang; Tian, Youli; Sohail, Amir; Khan, Muhammad Idrees; Xiao, Hua; Liu, Xiaoping; Wang, Yuxing; Li, Honggen; et al.
Abstract: As an effective separation tool, free‐flow electrophoresis has not been used for purification of low‐abundance protein in complex sample matrix. Herein, lysozyme in complex egg white matrix was chosen as the model protein for demonstrating the purification of low‐content peptide via an FFE coupled with gel fitration chromatography (GFC). The crude lysozyme in egg while was first separated via free‐flow zone electrophoresis (FFZE). After that, the fractions with lysozyme activity were condensed via lyophilization. Thereafter, the condensed fractions were further purified via a GFC of Sephadex G50. In all of the experiments, a special poly(acrylamide‐ co‐acrylic acid) (P(AM‐co‐AA)) gel electrophoresis and a mass spectrometry were used for identification of lysozyme. The conditions of FFZE were optimized as follows: 130 μL/min sample flow rate, 4.9 mL/min background buffer of 20 mM pH 5.5 Tris‐Acetic acid, 350 V, and 14 °C as well as 2 mg/mL protein content of crude sample. It was found that the purified lysozyme had the purity of 80% and high activity as compared with its crude sample with only 1.4% content and undetectable activity. The recoveries in the first and second separative steps were 65% and 82%, respectively, and the total recovery was about 53.3%. The reasons of low recovery might be induced by diffusion of lysozyme out off P(AM‐co‐AA) gel and co‐removing of high‐abundance egg ovalbumin. All these results indicated FFE could be used as alternative tool for purification of target solute with low abundance.